DENTAL FLUOROSIS - WORLDWIDE EPIDEMIOLOGICAL ASPECTS. REVIEW - Alexandru Flondor; Maria-Alexandra Martu; George-Alexandru Maftei; Ionut Botezatu; Eugen Mihalas; Laura Vasalca-Gavrila; Carmen Savin; Vasilica Toma (Romanian Dental Association for Education, 2021)
Fluoridation plays a key role in the prevention and control of dental caries in general public health. However, this success is not without cost and has resulted in strong debates within the dental profession. Dental fluorosis is a cosmetic effect that ranges in appearance from scarcely discernible to a marked staining or pitting of the teeth in severe forms. It is caused by an elevated fluoride level in, or adjacent to, the developing enamel, usually from birth to approximately six to eight years of age. Dental fluorosis in an adult is a result of high fluoride exposure when the adult was a child or adolescent. In its mildest (and most common) form it may manifests barely noticeable whitish striations, while more severe forms involve confluent pitting and staining of the dental enamel. The American Dental Association (ADA) defines it as a hypomineralization of tooth enamel that results from excessive fluoride ingestion prior to tooth eruption (ADA Reports, 2005). An increase in the prevalence of dental fluorosis has been reported simultaneously in both fluoridated and non-fluoridated communities. Although most of fluorosis is mild or very mild, and has little or no impact on quality of life of affected people, a judicious use of fluoride to avoid moderate and severe fluorosis is needed. In order that the maximum benefit of fluoride for caries control can be achieved with a minimum risk of side effects, it is necessary to have a comprehensive understanding of the mechanisms by which fluoride promotes caries control, thus regulating the amount of fluoride intake is essential.